Does the Athletes' Leg Muscle Power Increase After the Tabata Aquatic Program? - Ruslan Abdul Gani; Irfan Zinat Achmad; Rekha Ratri Julianti; Edi Setiawan; Zsolt Németh; Abdurrohman Muzakki; Novi Yanti; Habibie Habibie (OVS LLC, 2022)
The study purpose. This study aims to evaluate the effect of the Tabata aquatic training method program in increasing the muscle power of beginner level athletes. Materials and methods. The researcher used a mixed method in this study. There were twenty swimming athletes (n = 20, age: 14.40 ± 1.18 years, height: 169.20 ± 3.18 cm, weight: 62.20 ± 2.26 kg) who agreed to participate in this study and were divided into two groups. The treatment group (n = 10) received the Tabata aquatic program and the control group (n = 10) swam every day without participating in any physical activity. The Tabata aquatic program was carried out for 9 weeks with a frequency of 3 times a week. After implementing the Tabata aquatic program, 10 athletes were interviewed. This study applied a quantitative research instrument, including squat jumps, and a qualitative research instrument, including individual in-depth interviews lasting for 30 minutes each. Analysis of quantitative data using IBM SPSS version 25.0 and qualitative data using thematic analysis was applied. Results. Quantitative study results showed that there was a significant increase in the squat jumps test (leg muscle power) in the treatment group and vice versa, there was no increase in the control group. However, in qualitative research results, most participants mentioned that the Tabata aquatic program is a fun training method and has a positive effect.  Conclusions. After carrying out the Tabata aquatic program for 9 weeks, we confirmed that this training method has a great impact on improving athletes' leg muscle power in swimming.